Phenomenon of vaping in Generation Z women - Renaldi, Teuku; Pranata, Agung; Novirianthy, Rima; Masturah, Shabrina; Qurasifa, Sabila; Soenoe, Medika BN.; Ezigbo, Eyiuche D.; Pratama, Rovy (Trends in Infection and Global Health, 2024)
The vaping phenomenon among Generation Z (Gen Z) women has increased in popularity as an alternative to traditional cigarettes. As a group that has grown up in the digital era, they have easier access to information via the internet and social media, which has influenced their lifestyles and choices, including when it comes to smoking and vaping. The aim of this study was to understand how the vaping phenomenon affects Gen Z women. To address this question, our research provides an overview of the vaping-related phenomena occurring among Gen Z women. We conducted a literature review of eight publications covering five years, 20192024. The data indicated phenomena such as an increase in the number of vape users among women and an increase in aggressive vape advertising. Our study also explored the factors that lead to this phenomenon occurring and how the surrounding environment plays a very large role in this issue. Data suggested that the increase in vaping among Gen Z women is primarily due to environmental and peer influence factors. Therefore, to have better prevention and intervention strategies, peer influence should be taken into account.